Telegram Confirming that Red Cross is the Agency to Implement the United Nations Relief Program - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Red Cross Executive Committee Distribution will be carried out without discrimination and on the basis of need; the committee will supply all organizational, supervisory, technical personnel, services and equipment required for the operation of the program.